2018
DOI: 10.1159/000494783
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment Paradigm for Glutamate

Abstract: Background: Re-evaluation of the use of glutamic acid and glutamate salts (referred to as glutamate hereafter) by the European Food Safety Authority (EFSA) proposed a group acceptable daily intake (ADI) of 30 mg/kg body weight (bw)/day. Summary: This ADI is below the normal dietary intake, while even intake of free glutamate by breast-fed babies can be above this ADI. In addition, the pre-natal developmental toxicity study selected by EFSA, has never been used by regulatory authorities worldwide for the safety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 42 publications
0
25
0
3
Order By: Relevance
“…In addition, such an ADI of 30 mg of free additive glutamate/kg bw/day is at a level below the normal dietary free glutamate intake for toddlers and children (even in breastfed infants), as mentioned above in Table 1. On the basis of glutamate literature, and particularly on toxicokinetic data, Roberts et al [62] proposed to reduce the uncertainty factor for interspecies differences between rat and man from 10 to 2.5 given that the toxicokinetics of glutamate, when given as a bolus dose or administered as part of the diet, is similar in both species. In addition, instead of defining a NOAEL from the Vorhees study [57], they suggested to define it from the 3-generation reproductive study in mice of Anantharaman [54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, such an ADI of 30 mg of free additive glutamate/kg bw/day is at a level below the normal dietary free glutamate intake for toddlers and children (even in breastfed infants), as mentioned above in Table 1. On the basis of glutamate literature, and particularly on toxicokinetic data, Roberts et al [62] proposed to reduce the uncertainty factor for interspecies differences between rat and man from 10 to 2.5 given that the toxicokinetics of glutamate, when given as a bolus dose or administered as part of the diet, is similar in both species. In addition, instead of defining a NOAEL from the Vorhees study [57], they suggested to define it from the 3-generation reproductive study in mice of Anantharaman [54].…”
Section: Discussionmentioning
confidence: 99%
“…In other studies where 5,000 mg of MSG was given included in meals (about 70 mg/kg bw/day for a 70 kg person), this MSG symptom complex has not been linked to the addition of MSG to food [60, 61]. Hence, there is no substantive evidence to demonstrate that symptoms associated with MSG symptom complex occur to any extent when glutamate is consumed as part of the diet [62]. By the way, glutamate has been administered in experiments, in most cases to adults as a single, oral dose up to 160 mg/kg bw [22, 46, 63], but also chronically, for up to 6 weeks at daily doses up to 150,000 mg/day (about 2,000 mg/kg bw/day for a 70 kg person) without any deleterious effects: no clinical pathological changes, the only biochemically demonstrable effect was a decrease in serum cholesterol and associated beta lipoproteins [64].…”
Section: Safety Datamentioning
confidence: 99%
“…However, when enhancing palatability, it is of paramount importance to ensure that food additives will not cause harm to consumers. The safety of Monosodium Glutamate consumption and its acceptable doses has been reviewed extensively in the last twenty years by several regulatory organizations and expert bodies backed by data from empirical studies (Cynoberet al, 2018;Roberts et al, 2018). These research findings still leave room for further studies hence this research.…”
Section: Discussionmentioning
confidence: 99%
“…While human safety data are limited, subchronic rodent toxicological studies of both phenylalanine and serine have already been published [21,22]. However, in the case of macronutrients such as amino acids, rodent findings have limited applicability to human risk assessment [23,24]. Macronutrients are not substances added to foods at milligram levels, such as newly developed flavors or artificial sweeteners that can indeed be studied in rodent tests at several hundred times their estimated human exposure.…”
Section: Sleep Quality Mental Fatigue Macronutrient and Caloric Intakes Body Weight Changesmentioning
confidence: 99%
“…Macronutrients, including proteinogenic amino acids, have a long evolutionary history in foods and are ingested from regular food sources at doses of grams per day [1-3]. Feeding laboratory animals amino acids at amounts that are a hundred times higher than the regular dietary intake in order to use cross-species safety factors triggers non-specific and toxicologically irrelevant findings (e.g., a decrease in food intake) [23][24][25]. Therefore, animal data have limited relevance to human tolerance and interpretations of the current trials includes only human data.…”
Section: Sleep Quality Mental Fatigue Macronutrient and Caloric Intakes Body Weight Changesmentioning
confidence: 99%